2013
DOI: 10.4269/ajtmh.12-0664
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Educational Interventions to Enhance the Adoption of Fee-Based Arsenic Testing in Bangladesh: A Cluster Randomized Controlled Trial

Abstract: Abstract. Arsenic (As) testing could help 22 million people, using drinking water sources that exceed the Bangladesh As standard, to identify safe sources. A cluster randomized controlled trial was conducted to evaluate the effectiveness of household education and local media in the increasing demand for fee-based As testing. Randomly selected households (N = 452) were divided into three interventions implemented by community workers: 1) fee-based As testing with household education (HE); 2) fee-based As testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…DPHE/UNICEF, 2011; George et al, 2013) is clearly needed to promote the testing of wells that continue to be installed not only in Araihazar but throughout Bangladesh and a halfdozen neighboring countries where groundwater can also be high in As. One possibility may be to tie testing with the decision to install a new well by disseminating at the village level the information that is available for targeting a local low-As aquifer.…”
Section: Resultsmentioning
confidence: 99%
“…DPHE/UNICEF, 2011; George et al, 2013) is clearly needed to promote the testing of wells that continue to be installed not only in Araihazar but throughout Bangladesh and a halfdozen neighboring countries where groundwater can also be high in As. One possibility may be to tie testing with the decision to install a new well by disseminating at the village level the information that is available for targeting a local low-As aquifer.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the lack of institutional support, well-sharing is only moderately psychologically accepted (Inauen et al, 2013a), and well-testing services -the prerequisite for identifying arsenic-safe wells -are not readily locally available. Nevertheless, recent research has yielded encouraging results in this regard; people have been shown to pay for arsenic testing when provided with arsenic education (George et al, 2013), and behavior change interventions have been shown to successfully increase people's switching to neighboring safe wells (Inauen and Mosler, 2013). Until private or public safe water supply is extended to the entire population at risk of arsenic consumption, sharing of safe shallow tubewells will remain an important tool in reducing exposure and consequent adverse health impacts.…”
Section: Discussion and Synthesismentioning
confidence: 98%
“…Community interventions in Bangladesh have had success in motivating arsenic testing in severely affected areas, especially when coupled with household education. 6 A 2005 community-based intervention in the Quebec region succeeded at motivating more people to test for arsenic than a mass media campaign; however, while the proportion of well owners who had their water tested increased by four times, the total testing rate was only 16%. 7 Quebec residents who were already aware of problems related to drinking water (such as the need for microbiological analysis) were more likely to test for arsenic too.…”
Section: Discussionmentioning
confidence: 99%